ECOLOGICAL PROTECTION OF AGRICULTURE THROUGH SERBIAS LEGAL REGULATIONS AND JUDICIAL PRACTICE - Petrović, Zdravko; Jović, Vojislav; Manojlović, Dragan (Economics of Agriculture, 2015)
Within the codifcation of Crminal law of Republic of Serbia, which was conducted in 2005, legal protection of agriculture was introduced into ecological delicti which were then emphasised by having them unifed in the sole Head of the Criminal code as well as by partially aggravating penal policy. Certain criminal offences, which prior to the codification were a part of a different feld of legal protection, are now listed in the ecological delicti catalogue, and that positions them, according to the number of listed deliciti, on a very high place in comparisson to the other groups of criminal offences. Within the ecological delicti, there is a total of 18 (eighteen) offences,which are divided into 4 (four) groups depending on the object of legal protection. In this paper, besides the introductory conceptual defning the object of research, we described the normative arrangement of all the ecological delicti, within the agricultural protection, by researching their essential elements which include the capital and the qualifed form of execution, perpetrators features, type of responsability and penalty. Empirical research covers the four year period, more precisely the years 2009 -2012, according to the parameters related to the number of adult persons accused for criminal offenses against the environment which are endangering agriculture, or the number of accused and convicted persons, shown globally and individually according to the structure criminal offenses. Furthermore the research includes the penal policy which reffers to the allready stated penalties, that is- jail sentences and their duration, and that also is depicted individually and globaly according to the criminal offences structure.